2022
DOI: 10.3389/fped.2022.895408
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Kawasaki Disease Before and After the COVID-19 Pandemic in a Large Pediatric Heart Disease Center

Abstract: BackgroundKawasaki disease (KD) is an acute febrile systemic vasculitis of unknown etiology. After the pandemic of coronavirus disease 2019 (COVID-19), some children infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) showed clinical symptoms similar to KD, indicating a close relationship between KD and SARS-CoV-2. Therefore, we designed this retrospective study to analyze the characteristics of KD patients before and after the COVID-19 pandemic.MethodsWe retrospectively collected demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Importantly, coronary artery outcomes remained unchanged, as has been found in the other studies (13) (25).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Importantly, coronary artery outcomes remained unchanged, as has been found in the other studies (13) (25).…”
Section: Discussionsupporting
confidence: 82%
“…Although we have found no signi cant decrease in the age of onset, as did one of the Japanese studies (17), and we have found that the proportion of children under the age of 1 year did not vary, multiple other studies did not replicate our ndings. Instead, they showed a greater proportion of KD incidence in children under 1 year of age and, inversely, a smaller proportion of children between 1 and 5 years of age ( 14) (16), thus nding a decrease in their median age (18) (25). This phenomenon has been explained by older children changing lifestyles during the pandemic, such as lessened time outdoors and mask wearing, whereas younger children did not undergo as drastic lifestyle changes in comparison to before the pandemic (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, these major outbreaks self-stabilized, regardless of vaccination status. During the major outbreaks in 2022, there was a shift towards infecting younger populations [73][74][75], particularly those with vitamin D deficiency. These factors contribute to the dominant Omicron variants, increasing hospitalization but fewer deaths.…”
Section: Vitamin D Deficiency Increases the Vulnerability To Sars-cov-2mentioning
confidence: 99%